2011
DOI: 10.1785/0120100058
|View full text |Cite
|
Sign up to set email alerts
|

Models of Stochastic, Spatially Varying Stress in the Crust Compatible with Focal-Mechanism Data, and How Stress Inversions Can Be Biased toward the Stress Rate

Abstract: IntroductionIn her comment (Hardebeck, 2015) on our stress heterogeneity article (Smith and Heaton, 2011), Hardebeck suggests a different focal-mechanism error distribution than what we used in our 2011 article and suggests that this new error distribution will reduce our estimates of stress heterogeneity. In response to this, we have rerun our calculations three ways: (1) with the original mechanism error distribution from Smith and Heaton (2011), (2) with a mechanism error distribution similar to the one pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
54
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 48 publications
3
54
0
3
Order By: Relevance
“…The findings suggest that the magnitudes of differential stresses are much smaller than expected from results of frictional experiments in laboratories (Byerlee 1978), which Smith and Heaton (2011) regard as artifacts, as they reflect stress changes (incremental stress) generated by earthquake slips. However, Hardebeck (2010) reported results that contradict the view of Smith and Heaton (2011). They estimated stress fields before and after large earthquakes based on stress inversion of focal mechanisms and showed that the focal mechanisms of aftershocks are mainly controlled by the stress before large earthquakes.…”
Section: Introductionmentioning
confidence: 67%
See 4 more Smart Citations
“…The findings suggest that the magnitudes of differential stresses are much smaller than expected from results of frictional experiments in laboratories (Byerlee 1978), which Smith and Heaton (2011) regard as artifacts, as they reflect stress changes (incremental stress) generated by earthquake slips. However, Hardebeck (2010) reported results that contradict the view of Smith and Heaton (2011). They estimated stress fields before and after large earthquakes based on stress inversion of focal mechanisms and showed that the focal mechanisms of aftershocks are mainly controlled by the stress before large earthquakes.…”
Section: Introductionmentioning
confidence: 67%
“…Smith and Heaton (2011) proposed that they reflect not the orientations of the three principal stresses but those of incremental stresses, as shown in Fig. 1b.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations